Cytotoxic Activity of Curcuminoids and Curcuminoid Analogues Against Human Oral Cancer KB Cells** - Haritakun, Woraphot; Changtam, Chatchawan (Journal of Food Health and Bioenvironmental Science, 2019)
The natural curcuminoids, curcumin (1), demethoxycurcumin (2) and bisdemethoxycurcumin (3), have been structurally modified to the demethylated analogues 4-6, methylated analogues 7-12, acetylated analogues 13-17 and the tetrahydro analogues 18-21. The curcuminoids 1-3 and the analogues 4-21 were evaluated for their cytotoxic activities against a human oral cancer (KB) cell line. The demethylated analogues 4-6 and methylated analogues 7-8 exhibited high cytotoxic activities against KB cells with IC50 values of 7.76, 2.38, 8.17, 7.11 and 3.85 μM, respectively. Interestingly, the analogue 5 exhibited the highest cytotoxicity (IC50 value 2.38 μM), which was more potent than ellipticine, the reference anticancer drug (IC50 value 5.40 μM). For the acetylated analogues, the results showed that acetylation did not increase cytotoxicity of the parent curcuminoids. Furthermore, it was also found that the tetrahydro analogues were inactive in this study. The results indicated that conjugated diketo system is essential for cytotoxicity. Analogues with more of free hydroxyl groups were more potent than the natural curcuminoids, with exception for the mono-O-methyl and di-O-methyl analogues of curcumin.